2007
DOI: 10.1016/j.juro.2007.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections and Bladder Dysfunction After Renal Transplantation in Children

Abstract: Bladder dysfunction did not predispose patients to recurrent urinary tract infections. Graft function declined with time in all patients but the rate of deterioration was faster in the group with recurrent urinary tract infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 13 publications
3
27
1
1
Order By: Relevance
“…In a meta-analysis, Green et al [42] reported that antibiotic prophylaxis reduced the sepsis with bacteraemia by 87% and the bacteriuria by 60%. Herthelius et al [36] reported that the incidence of recurrent UTIs was 35 and 42% in recipients with and without bladder dysfunction, respectively, in a study in 68 children after a mean follow-up of 6 years. This difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis, Green et al [42] reported that antibiotic prophylaxis reduced the sepsis with bacteraemia by 87% and the bacteriuria by 60%. Herthelius et al [36] reported that the incidence of recurrent UTIs was 35 and 42% in recipients with and without bladder dysfunction, respectively, in a study in 68 children after a mean follow-up of 6 years. This difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…They are the most common form of bacterial infections after RTx [36][37][38][39]. Some authors found no influence of UTI on graft survival [16,40], while others have stated that febrile infectious episodes may have an adverse impact on long-term renal graft function [41].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a two-centre study failed to document any difference in serum creatinine after a follow-up time of 3.3 years between a cohort of children who had one or more episode of UTI post-KTx and those who did not [3]. Some researchers have suggested that post-KTx UTI adversely affects graft function and that the failure to detect a difference in graft function between a group of children who developed post-KTx UTI and those who did not may be due to the poor sensitivity of serum creatinine as a marker for detecting decreased GFR [6,19]. Using inulin and iohexol, Herthelius and Oborn reported that having more than one episode of post-KTx UTI was associated with decreased graft function [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have suggested that post-KTx UTI adversely affects graft function and that the failure to detect a difference in graft function between a group of children who developed post-KTx UTI and those who did not may be due to the poor sensitivity of serum creatinine as a marker for detecting decreased GFR [6,19]. Using inulin and iohexol, Herthelius and Oborn reported that having more than one episode of post-KTx UTI was associated with decreased graft function [19]. Our inability to detect a difference in the most recent serum creatinine between the two groups of children may also be due to the high number of non-E. coli UTI.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent retrospective study from Herthelius et al [33, 34] suggested no increased frequency of UTI after KTX in children with bladder dysfunction. However, the study did not analyze the effect of interventions in the patients with voiding dysfunction.…”
Section: Risk Factorsmentioning
confidence: 98%